The relationship between passion and imagery use in competitive youth gymnastics - Simpson, J.; Munroe-Chandler, K. J.; Paradis, K. F. (Science of Gymnastics Journal, 2020)
The purpose of the present study was to examine the relationship between passion and imagery use in competitive youth gymnastics. The participants included 245 (male, n = 10; female, n = 235) gymnasts between the ages of 7-16 years participating in women`s artistic gymnastics (n = 221), men`s artistic gymnastics (n = 7), as well as trampoline and tumbling (n = 17). Athletes completed questionnaires measuring the frequency of imagery use and their passion towards the sport of competitive gymnastics. A series of multiple regression analyses indicated that both harmonious and obsessive passion were significantly related to all five types of imagery. More specifically obsessive passion was most strongly associated with four of the five types of imagery (CS, CG, MS, and MG-A), and harmonious passion was most strongly associated with one of the five types of imagery (MG-M). Results and implications of passion and imagery use in competitive youth sport are discussed.